Hyperinsulinemia impairs the metabolic switch to ketone body utilization in proximal renal tubular epithelial cells under energy crisis via the inhibition of the SIRT3/SMCT1 pathway - Xie, Jinlan; Zhong, Feifei; Guo, Zhenhong; Li, Xinran; Wang, Jingyu; Gao, Zhongai; Chang, Baocheng; Yang, Juhong (Frontiers in Endocrinology, 2022)
Objective: To investigate the effects and mechanism of hyperinsulinemia on the metabolic switch to β‐hydroxybutyrate (BHB) absorption and utilization under starvation or hypoxic environment in proximal tubular epithelial cells. Methods: A high-fat diet induced hyperinsulinemia model in ZDF rats was used to test the expression of key enzymes/proteins of ketone body metabolism in the kidney. Notably, 12-week-old renal tubule SMCT1 specific knockout mice (SMCT1 flox/floxCre+) and control mice (SMCT1 flox/floxCre-) were used to confirm the roles of SMCT1 in kidney protection under starvation. The changes of key enzymes/proteins of energy metabolism, mitochondrial function, and albumin endocytosis in HK2 cells under low glucose/hypoxic environments with or without 50 ng/ml insulin were studied. Silent information regulation 2 homolog 3 (SIRT3) was overexpressed to evaluate the effect of hyperinsulinemia on the metabolic switch to BHB absorption and utilization through the SIRT3/SMCT1 pathway in HK2 cells. Results: In ZDF rats, the expression of HMGCS2 increased, the SMCT1 expression decreased, while SCOT remained unchanged. In renal tubules specific SMCT1 knockout mice, starvation for 48 h induced an increase in the levels of urine retinol-binding protein, N-acetyl -β -glucosaminidase, and transferrin, which reflected tubular damages. In HK2 cells under an environment of starvation and hypoxia, the levels of key enzymes related to fatty acid oxidation and ketone body metabolism were increased, whereas glucose glycolysis did not change. The addition of 2 mmol/L BHB improved ATP production, mitochondrial biosynthesis, and endocytic albumin function, while cell apoptosis was reduced in HK2 cells. The addition of 50 ng/ml insulin resulted in decreased expression of SMCT1 along with an impaired mitochondrial function, decreased ATP production, and increased apoptosis. The overexpression of SIRT3 or SMCT1 reversed these alterations induced by a high level of insulin both in low glucose and hypoxic environments. Conclusions: The increased absorption and utilization of BHB is part of the metabolic flexibility of renal tubular epithelial cells under starvation and hypoxic environments, which exhibit a protective effect on renal tubular epithelial cells by improving the mitochondrial function and cell survival. Moreover, hyperinsulinemia inhibits the absorption of BHB through the inhibition of SIRT3/SMCT1 pathway.